Feeling Blue and Getting Red: An Exploratory Study on the Effect of Color in the Processing of Emotion Information - Kang, June; Park, Yeo Eun; Yoon, Ho-Kyoung (Frontiers in Psychology, 2022)
Specific emotions and colors are associated. The current study tested whether the interference of colors with affective processing occurs solely in the semantic stage or extends to a more complex stage like the lexical processing of emotional words. We performed two experiments to determine the effect of colors on affective processing. In Experiment 1, participants completed a color-emotion priming task. The priming stimulus included a color-tinted (blue, red, and gray) image of a neutral face, followed by a target stimulus of gray-scaled emotional (angry and sad) and neutral faces after 50 ms. Experiment 2 used a modified emostroop paradigm and superimposed emotion words on the center of the color-tinted emotional and neutral faces. Results showed the priming effect of red for the angry face compared to the control, but not in blue for the sad face compared to the control. However, responses to the blue-sad pair were significantly faster than the red-sad pair. In the color-emostroop task, we observed a significant interaction between color and emotion target words in the modified emostroop task. Participants detected sad targets more accurately and faster in blue than red, but only in the incongruent condition. The results indicate that the influence of color in the processing of emotional information exists at the semantic level but found no evidence supporting the lexical level effect.